Understanding Corn Quality Control Process UD Dicky Putra - Puspitasari, Adelia (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Objective: To analyze the quality control process of corn. Methods: In this study, researchers used descriptive qualitative methods. Data collection was done by interview, observation and documentation techniques. Data analysis with data reduction. Research Findings: The study found that the process of controlling corn includes raw material selection, drying process, and preserved storage. Theoretical      contribution/Originality:      This      research      provides additional insights in the literature review on quality control in the agribusiness sector, especially related to corn processing and storage. Practice/Policy Implications: This research has practical implications that can be applied by similar businesses. Research limitations: The limitation of this study lies in the relatively short duration of research time, so the scope of analysis is limited. Keywords: Quality control, qualitative, quality management